GE_GERICHTE C/14537/2016 vom 21. Januar 2019 - GE Cour de justice (2019)
BAIL À LOYER ; CALCUL ; RENDEMENT BRUT ; INSPECTION LOCALE ; CHOSE LOUEE ; DÉFAUT DE LA CHOSE | CPC.317.al2; CPC.227.al1; CPC.150.al1; CPC.152; CO.259a; CO.259d